If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2x + -7y + 4) = 0 Reorder the terms: -1(4 + 2x + -7y) = 0 (4 * -1 + 2x * -1 + -7y * -1) = 0 (-4 + -2x + 7y) = 0 Solving -4 + -2x + 7y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + -2x + 4 + 7y = 0 + 4 Reorder the terms: -4 + 4 + -2x + 7y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -2x + 7y = 0 + 4 -2x + 7y = 0 + 4 Combine like terms: 0 + 4 = 4 -2x + 7y = 4 Add '-7y' to each side of the equation. -2x + 7y + -7y = 4 + -7y Combine like terms: 7y + -7y = 0 -2x + 0 = 4 + -7y -2x = 4 + -7y Divide each side by '-2'. x = -2 + 3.5y Simplifying x = -2 + 3.5y
| 3r+25=-1 | | 19x=-20 | | (7+v)(2v-9)=0 | | -4z+7=-6z-29 | | 4b+6=-12 | | 19=-16+x | | 13/8=x/5 | | -6x-3=-3-7(1+x) | | r-(17.5-19r)t=5t^2 | | Ax-7b=2c | | (x+1)*(x-1)=0 | | 40-8m=-8(m-5) | | 40-8m=8(m-5) | | 5q^2+8q=12 | | (5x-1)*(x-1)=0 | | 2x-97=x+4 | | -8+2x=4x-6 | | 2x-95=x+4 | | 6x+8-x=-47 | | 3=5(x-4)+1-4x | | -4x-x=11(4x-11)+4(4-11x) | | 3=5(x-4)*1-4x | | 6m+3n+4m+8n= | | y=x^2-6x+k | | f(x+4)=x^2+2x-8 | | 5-3y+y= | | 65-13.5(0.2P-1.5)=7.5 | | 0.05P+0.07(1200-P)=80 | | 11(1-9x)=-7-12(5x-8) | | -5x+4y= | | 3/6-2/15 | | 152.34=2.95h+72.69 |